2014
DOI: 10.1007/s00109-014-1211-9
|View full text |Cite|
|
Sign up to set email alerts
|

Angiotensin II stimulates canonical TGF-β signaling pathway through angiotensin type 1 receptor to induce granulation tissue contraction

Abstract: Hypertrophic scar contraction (HSc) is caused by granulation tissue contraction propagated by myofibroblast and fibroblast migration and contractility. Identifying the stimulants that promote migration and contractility are key to mitigating HSc. AngiotensinII (AngII) promotes migration and contractility of heart, liver, and lung fibroblasts; thus, we investigated the mechanisms of AngII in HSc. Human scar and unwounded dermis were immunostained for AngII receptors AT1-receptor and AT2-receptor, and analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…It has been largely demonstrated that TGF-beta serves as a key downstream mediator in Ang II-induced chronic renal fibrosis (Iekushi et al, 2011). Fibrosis resulting in the excessive synthesis and accumulation of interstitial matrix proteins could be induced by Ang II via the upregulation of TGF-beta (Ehanire et al, 2015a;Ding et al, 2019). Consistent with these findings, our data showed that following Ang II infusion, the expression of fibrotic markers alpha-SMA, MMP-2, and MMP-9 were all significantly increased (Figures 1A-F).…”
Section: Discussionmentioning
confidence: 99%
“…It has been largely demonstrated that TGF-beta serves as a key downstream mediator in Ang II-induced chronic renal fibrosis (Iekushi et al, 2011). Fibrosis resulting in the excessive synthesis and accumulation of interstitial matrix proteins could be induced by Ang II via the upregulation of TGF-beta (Ehanire et al, 2015a;Ding et al, 2019). Consistent with these findings, our data showed that following Ang II infusion, the expression of fibrotic markers alpha-SMA, MMP-2, and MMP-9 were all significantly increased (Figures 1A-F).…”
Section: Discussionmentioning
confidence: 99%
“…The male diabetic (BSK.Cg-m+/+Lepr db ; db/db) and WT mice (C57BL/6J) were 10 weeks old at the beginning of the experiments; db/db mice weighed 55-60 g with average blood glucose levels of 26.8 ± 0.6 mmol/L and WT mice weighed 20-25 g with average blood glucose levels of 6.1 ± 0.4 mmol/L. The skin wound study was performed as previously described [29]. Briefly, after shaving the chosen area of the dorsal surface under anesthesia, a circular fullthickness excisional skin wound of 8-mm diameter was created using a surgical punch.…”
Section: Wound Healing In Vivomentioning
confidence: 99%
“…This can also be explained by up-regulation of TGF-β, because TGF-β has been reported to stimulate differentiation of fibroblasts to myofibroblasts [ 23 ], which play a major role in tissue shrinking/contraction in the wound healing process. Also, it was reported that stimulation of the TGF-β signaling pathway by angiotensin II induces granulation tissue contraction via the angiotensin type 1 receptor [ 51 ]. Thus, the present data also showed that induction of TGF-β by topical application of lavender oil promotes not only formation of granulation tissue, but also wound shrinking/contraction.…”
Section: Discussionmentioning
confidence: 99%